I'm currently working on a problem that involves a Z-Transform. Basically, the essence of the problem is that if: \begin{equation} H\left(z\right) = \sum_{n=0}^{N-1}h\left(n\right)z^{-n} \end{equation} find: \begin{equation} Y\left(z\right)\:=\:H\left(z\right)\cdot H^*\left(\frac{1}{z^*}\right) \end{equation} The asterisk represents a complex conjugate. So, I know that

\begin{equation} H^*\left(\frac{1}{z^*}\right)\:=\:\sum _{n=0}^{N-1}h^*\left(n\right)z^n \end{equation} Am stuck at this part now: \begin{equation} Y\left(z\right)=\left(\sum_{n=0}^{N-1}h\left(n\right)z^{-n}\right)\left(\sum_{n=0}^{N-1}h^*\left(n\right)z^n\right) \end{equation}

I'm stuck at this part and don't know what to do from here. Thank you for your help in advance.

  • $\begingroup$ You may try treating that product in Z as a convolution in time. $\endgroup$
    – Juancho
    Sep 2, 2020 at 15:38
  • $\begingroup$ Polynomial multiplication is equivalent to convolution. math.stackexchange.com/questions/1937630/… $\endgroup$
    – ZR Han
    Sep 29, 2021 at 4:24

1 Answer 1


This may help: the result is the cascade of an FIR filter with coefficients $h(n)$ with the reverse conjugate filter with coefficients $h^*(N-n)$. If we can limit $H(z)$ to be the unit circle (for computing the frequency response), then

$$H(z^*)|_{z=e^{j\omega}} = H(z^{-1})|_{z=e^{j\omega}}$$


for $z = e^{j\omega}$, $z^* = e^{-j\omega}$

And therefore

$$H^*(1/z)|_{z=e^{j\omega}}= H^*(z^*)|_{z=e^{j\omega}}$$


$$H^*(1/z^*)|_{z=e^{j\omega}}= H^*(z)|_{z=e^{j\omega}}$$


$$Y(z)|_{z=e^{j\omega}} = H(z)H^*(z)|_{z=e^{j\omega}} = |H(z)|^2|_{z=e^{j\omega}}$$

Also from the link the OP provided to me in the comments below, it is clear that the problem is dealing with the two sided Z-transform and the full problem has a solution given as

$$H(z)H^*(1/z^*)\Phi_{xx}(z) = \frac{\sigma_v^2}{(1-az^{-1})(1-a^*z)}$$

And we see from the earlier solution in the link that

$$H(z) = \frac{1}{1-az^{-1}}$$


$$H^*(z) = \frac{1}{1-a^*(1/z^*)}$$


$$H^*(1/z) = \frac{1}{1-a^*(z^*)}$$


$$H^*(1/z^*) = \frac{1}{1-a^*z}$$



Note confirming my earlier result, when we restrict z to be the unit circle (for determining the magnitude response):

$$H^*(z)|_{z=e^{j\omega}} = \frac{1}{1-a^*(1/z^*)}|_{z=e^{j\omega}}= \frac{1}{1-a^*(1/e^{-j\omega})} = \frac{1}{1-a^*(e^{j\omega})} = \frac{1}{1-a^*z}|_{z=e^{j\omega}}$$

Also to avoid any confusion, earlier in the linked solutions where it says "from 7... we arrive at (2.55) as follows" it gives a result that indicates

$$\Phi_{xx}(z) = \Phi^*_{xx}(1/z^*)$$

But this is not generally true for any z transform, (we cannot conclude that $H(z) = H^*(1/z^*)$ for all z) but it is in this case specific to the autocorrelation function $\phi_{xx}(k)$ since that function is Hermitian:

$$\phi^*_{xx}(k) = \phi_{xx}(-k)$$

  • $\begingroup$ Thanks for the answer, but we can't assume an ROC. Also, this is not what the answer in the book is. $\endgroup$
    – JordenSH
    Sep 2, 2020 at 22:43
  • $\begingroup$ @Raykh what is the answer in the book? $\endgroup$ Sep 2, 2020 at 22:46
  • $\begingroup$ Well what I posted is a generic form of the problem, so the answer form would be different but was expecting the answer here to go inline with what the book has. $\endgroup$
    – JordenSH
    Sep 3, 2020 at 2:17
  • $\begingroup$ @Raykh Yes could you provide that? $\endgroup$ Sep 3, 2020 at 2:19
  • $\begingroup$ Sure thing. Please refer to below at problem 10 after the sentence that say "using 2.80" ebookyab.com/files/… $\endgroup$
    – JordenSH
    Sep 3, 2020 at 3:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.